Alterations in Biomarkers Associated with Cardiovascular Health and Obesity with Short-Term Lifestyle Changes in Overweight Women: The Role of Exercise and Diet - Senguen, Nezihe; Pala, Ragip; Cinar, Vedat; Akbulut, Taner; Larion, Alin; Padulo, Johnny; Migliaccio, Gian Mario (Mdpi, 2024)
Background and Objectives: In this study, the effects of an eight-week exercise and nutrition program on blood lipids, glucose, insulin, insulin resistance (HOMA-IR), leptin, ghrelin, irisin, malondialdehyde (MDA), and Growth Differentiation Factor 15 (GDF15) in overweight women were investigated. Materials and Methods: A total of 48 women volunteers participated in this study. The participants were randomly divided into four groups: control (C), exercise (E), nutrition (N), exercise + nutrition (E + N). While no intervention was applied to group C, the other groups participated in the predetermined programs for 8 weeks. At the beginning and end of this study, body composition was measured and blood samples were taken. Results: It was determined that the body composition components, lipid profile indicators, insulin, glucose, insulin resistance, leptin, ghrelin, irisin, and MDA parameters examined in this study showed positive changes in the intervention groups. Group E had a greater effect on body muscle percentage, MDA, and irisin levels, while group N had a greater effect on blood lipids and ghrelin levels. Conclusions: As a result, it is thought that lifestyle changes are important to improve cardiovascular health and combat obesity, and that maintaining a healthy diet together with exercise may be more effective.
Keywords: weight loss; exercise; nutrition; health; GDF15